2021
DOI: 10.1609/icwsm.v6i1.14278
|View full text |Cite
|
Sign up to set email alerts
|

The Livehoods Project: Utilizing Social Media to Understand the Dynamics of a City

Abstract: Studying the social dynamics of a city on a large scale has tra- ditionally been a challenging endeavor, requiring long hours of observation and interviews, usually resulting in only a par- tial depiction of reality. At the same time, the boundaries of municipal organizational units, such as neighborhoods and districts, are largely statically defined by the city government and do not always reflect the character of life in these ar- eas. To address both difficulties, we introduce a clustering model and researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Data from online location platforms captures human activity at high resolution. Accordingly, this type of data was instrumental in basic research on human dynamics, where it helped in identifying universal patterns of human urban mobility (Noulas et al 2012) and in discovering dynamic clusters of urban activity (Cranshaw, Hong, and Sadeh 2012).…”
Section: Mining Data From Online Location Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from online location platforms captures human activity at high resolution. Accordingly, this type of data was instrumental in basic research on human dynamics, where it helped in identifying universal patterns of human urban mobility (Noulas et al 2012) and in discovering dynamic clusters of urban activity (Cranshaw, Hong, and Sadeh 2012).…”
Section: Mining Data From Online Location Servicesmentioning
confidence: 99%
“…It is well established in scientific literature (Arribas-Bel and Bakens 2018) that data from online location services reflects only a subset of the general population -for instance, Foursquare users used to be young, professionals, smartphones owners back in 2012/2013 (Cranshaw, Hong, and Sadeh 2012). Another potential caveat could be that businesses may have artificially inflated their check-ins.…”
Section: Limitations and Potential For Future Researchmentioning
confidence: 99%
“…Urban computing using geotagged data Among the works that leverage geotagged data of particular interest are the tasks of finding local experts on Twitter (Cheng et al 2014), and characterizing city areas such as neighborhoods in terms of the local activities (Cranshaw et al 2012;Le Falher, Gionis, and Mathioudakis 2015). The latter two works are the most relevant to ours, and exploit data from location-based services.…”
Section: Related Workmentioning
confidence: 99%
“…In the domain of urban computing (Zheng et al 2014;Silva et al 2019), location-based social media has been shown as a useful means of identifying and understanding semantic areas of cities (Cranshaw et al 2012;Noulas et al 2011;Zhang and Zhou 2018), providing valuable insights into people's opinions to support the well-being status of urban communities (De Choudhury, Sharma, and Kiciman 2016;Venerandi et al 2015;Hecht and Stephens 2014). These results, demonstrating the utility of user generated content, have caught the attention of practitioners and policy-makers who aim to make cities more livable and equitable.…”
Section: Introductionmentioning
confidence: 99%